Catalytic Dinitrogen Reduction at the Molybdenum Center Promoted by a Bulky Tetradentate Phosphine Ligand1. (19th October 2014) - Liao, Qian; Saffon‐Merceron, Nathalie; Mézailles, Nicolas
Abstract Stoichiometric reduction of N2 at a Mo center stabilized by a bulky tetradentate phosphine ligand (<alternatives> <![CDATA[${{\rm PP}{{{\rm Cy}\hfill \atop 3\hfill}}}$]]> <inline-graphic xlink:href="ark:/27927/pgh2qxfg753" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /></alternatives>) allowed isolation of Mo–imidoamine and Mo–imido complexes. Both complexes as well as the MoII precursor are equally suitable catalysts for the synthesis of NTMS3 (TMS=trimethylsilyl) from N2, TMSCl, and electron sources. Mechanistic studies prove the involvement of a TMS radical at least in one of the catalytic steps.